EXTH-10. A VERSATILE AND MODULAR TARGETED NANOPARTICLE PLATFORM FOR DELIVERY OF COMBINATION THERAPIES TO ADULT AND PEDIATRIC CNS TUMORS. (5th November 2018) - Lam, Fred; Morton, Stephen; Wyckoff, Jeffrey; Vu Han, Tu-Lan; Hwang, Mun; Maffa, Amanda; Balkanska-Sinclair, Elena; Yaffe, Michael; Floyd, Scott; Hammond, Paula
Abstract: Effective treatment of CNS tumors is limited by the presence of the blood-brain barrier (BBB) and rapid resistance to single agent therapies. To address these issues, we developed nanoparticles (NPs) that can be functionalized with ligands, such as transferrin (Tf-NPs), for delivery across the BBB to deliver multiple cargo to CNS tumors. In vitro uptake studies in U87MG and GL261 GBM cell lines demonstrate increased intracellular uptake of Tf-NPs compared to non-functionalized NPs in a time-dependent manner. Using intravital imaging through a cranial window, we show the ability of Tf-NPs to traverse the intact BBB in non-tumor bearing mice as well as achieve direct and durable tumor binding in intracranial orthotopic models of U87MG and GL261 GBM. Treatment of tumor-bearing mice with Tf-NPs loaded with temozolomide (TMZ) and the bromodomain inhibitor JQ1 leads to superior therapeutic effects with increased DNA damage and apoptosis that correlates with a 1.5- to 2-fold decrease in tumor burden and corresponding increase in survival compared to mice treated with drugs packaged in non-functionalized NPs or mice treated with equivalent free-drug dosing. Immunocompetent mice treated with Tf-NP-loaded drugs also show relative protection from the effects of systemic drug toxicity due to TMZ and JQ1. Preliminary intravital imaging further shows the ability of our NPs to target pediatric tumors such as medulloblastoma, demonstrating the preclinical potential of this nanoscale platform to deliver novel combination therapies to adult and pediatric CNS tumors.